Carotenoid‐enriched transgenic corn delivers bioavailable carotenoids to poultry and protects them against coccidiosis. Issue 1 (2nd April 2015) - Nogareda, Carmina; Moreno, Jose A.; Angulo, Eduardo; Sandmann, Gerhard; Portero, Manuel; Capell, Teresa; Zhu, Changfu; Christou, Paul
Summary: Carotenoids are health‐promoting organic molecules that act as antioxidants and essential nutrients. We show that chickens raised on a diet enriched with an engineered corn variety containing very high levels of four key carotenoids (β‐carotene, lycopene, zeaxanthin and lutein) are healthy and accumulate more bioavailable carotenoids in peripheral tissues, muscle, skin and fat, and more retinol in the liver, than birds fed on standard corn diets (including commercial corn supplemented with colour additives). Birds were challenged with the protozoan parasite Eimeria tenella and those on the high‐carotenoid diet grew normally, suffered only mild disease symptoms (diarrhoea, footpad dermatitis and digital ulcers) and had lower faecal oocyst counts than birds on the control diet. Our results demonstrate that carotenoid‐rich corn maintains poultry health and increases the nutritional value of poultry products without the use of feed additives.